F(x) = 2x and G(x) = x^2 + 2
(G - F)(x) just means we subtract the functions from each other.
x^2 + 2 - 2x
Let's rearrange the expression
x^2 - 2x + 2
Answer:
16
Step-by-step explanation:
count each dot
X // Y, Y // Z,
By inference X // Z
The third option.
Answer:
42
Step-by-step explanation:
let the number be x
4/7 of x
(4/7) × x
4x/7
As stated in the question:
x=4x/7+18
=x-4x/7=18
=(7x-4x)/7=18
=3x/7=18
3x= 18×17
3x= 126
x=126/3
x=42
The relationship being proportional means there is a value of k such that
... y = k·x
We are given the point (6 (pounds), 3 (dollars)), so we can write ...
... 3 dollars = k·6 pounds
Dividing by 6 pounds, we get
... (3/6) dollars/pound = k = $0.50/lb
Now, we can use x=1 pound to find the price (y),
... y = ($0.50/lb)·(1 lb)
... y = $0.50 . . . . the price of 1 pound of tomatoes.